Digital Religiosity dan Teologi Kontekstual: Strategi Inovatif Menghidupkan Kembali Gereja bagi Kaum Muda - Pasaribu, Ferdinan; Sakidaat, Anetrin (Institut Agama Kristen Negeri Palangka Raya, 2025)
This article aims to explore the potential of digital religiosity alongside the application of contextual theology as an innovative strategy to rekindle young people’s interest in the church. By integrating digital technology into faith practices and contextualizing theological messages within local cultures, the church can present itself as more relevant and closely connected to the realities of today’s generation. The findings indicate that digital religiosity and theology shaped by digital-life contexts can provide a more relevant, participatory, and meaningful model of ministry for youth engagement. This study employs a qualitative method through literature research on religious phenomena and thoughts related to contextual theology. The conclusion affirms that the church’s renewed relevance among young people emerges when digital religiosity is developed through a theological approach that is responsive to digital realities, enabling the church’s ministry to be vibrant, creative, and meaningful for the present generation.